ANALISIS KOINTEGRASI DAN KAUSALITAS ENGEL GRANGER TINGKAT SUKU BUNGA SIMPANAN, PERUBAHAN NILAI TUKAR RP/USD DAN RETURN PASAR SAHAM DI BURSA EFEK INDONESIA - Pranyoto, Edi (Jurnal Bisnis Darmajaya, 2017)
The Engel Granger Test is a method to indicate the possibility of a short-term and long-term relationship between economic variables as required by economic theory. In the concept of cointegration, two variables non-stationary will be cointegrated when the combination is linear as well. The purpose of this study is to apply the test cointegration and test of Engel Granger causality to see whether there is a relationship of short-term and long-term interest rate, exchange rate, and stock market returns in Indonesia Stock Exchange before and after crisis Monetary Indonesia. This research used time series data of interest rate, exchange rate, and stock market return. The result showed that there is long-term equilibrium relationship between stock return variables, interest rates and exchange rate on the Indonesia Stock Exchange. The stock return has a short-term and long-term impact on the exchange rate in the Indonesian capital market. The development of the exchange rate before economic crisis of 1993-1997 showed a relatively stable condition. However, since the end of 1997 until the year 2015 showed a relatively unstable condition, increased and decreased. Similarly, the development of stock returns and savings interest rates increased and decreased over time. In other words the movement of these three data indicates high volatility, making it difficult to predict the movement of these variables.Keywords: cointegration, causality of engel granger, time series, interest rate,                   exchange rate, and stock market return